Investigation of the test–retest reliability and inter-rater agreement of traditional Chinese medicine-based pulse diagnosis among Indian traditional Chinese medicine practitioners - Mamta Jagwani; Gita Sharma; Hemanshu Sharma; Tara K Kafle; Gulab Rai Tewani; Pradeep M K. Nair (World Journal of Traditional Chinese Medicine, 2023)
Objective: The objective of this study was to assess the test–retest reliability and inter-rater agreement between the traditional Chinese medicine (TCM) pulse diagnosis between two Indian TCM practitioners. Methods: A total of 300 participants were evaluated for their bilateral pulse based on TCM independently by two investigators with similar years of experience but who graduated from different medical schools. The investigators who were blinded diagnosed the participants as per TCM based on the depth, rate, and strength of their pulse. Cronbach α and weighted kappa were used for assessing the reliability and repeatability. Results: The data of all the 300 participants were included in the analysis. The test–retest reliability computed using Cronbach's alpha indicated high reliability between the investigators (α =0.963). There were a total of 37 different types of diagnoses identified by both investigators. The investigators diagnoses matched for 116 participants out of 300 participants; whereas 184 cases were not matched between the investigators. The inter-rater agreement for the TCM diagnosis tested by weighted Kappa did not returned any significant agreement (Kappa = 0.370). Discussion: The present study shows higher reliability between the pulse diagnoses between the investigators. However, the inter-rater agreement for TCM diagnosis based on pulse diagnosis was not significant probably due to the variation in subjective assessments. This calls for the standardization of training in TCM diagnostic methods among practitioners. Future studies should include the differences in training, medical education, and experience among the practitioners while determining the reliability of pulse diagnosis.